Does the Visa-Free Policy Promote Inbound Tourism? Evidence From China - Jiafeng Gu (SAGE Open, 2024)
A visa-free policy is a tool for attracting foreign tourists, but existing studies evaluating its effects do not consider spatial spillover. This study, therefore, examined the effects of visa policies on urban inbound tourism with spatial spillover. This study used the implementation of the 72-hr visa-free transit policy in China as a natural experiment and employed a spatial difference-in-differences approach. The results show that the implementation of the 72-hr visa-free transit policy had no significant effect on the number of foreign tourists, but can reduce the average length of stay for foreign tourists. It also shows that there is a significant spatial spillover effect on the flow of foreign tourists. The results indicate the importance of spatial spillover in the evaluation of the impact of visa policy on inbound tourism, providing empirical evidence for further improving visa-free policies and urban tourism development.